Government Policy as a Driver of Energy Saving in Egypt - Bahgat, Hussameldeen (European Journal of Sustainable Development, 2016)
This study focuses on the Government policy and deals with the Egyptian urban problem which started in the middle of the twentieth century. In the past five decades, the government has adopted several urban development plans. Those plans have followed experiences of some developed countries which were not necessarily in line with the local conditions and priorities. In addition, governmental institutions have dealt with global trends of urban development such as the need of sustainability for the next generations. This, unfortunately, was done in a shallow way and without enough studies to determine the specific local needs and priorities. Moreover, barriers that hinder the urban development process have recently appeared. Since Egypt faces water shortage and fossil fuel crisis, the current strategies and policies, that are currently ineffective, need to be reorganized. This is just to solve the old common urban problems. This study discusses the need of the government to develop new national strategies and policies for energy saving using new approaches for sustainable urban development planning. It also discusses the need of the government to improve performance capacities and capabilities continuously. The improvement should be technological as well as organizational and social. Keywords: government policy; sustainability; developed countries.